a COMMUNITY EMPOWERMENT THROUGH PROCESSING FISH INTO NUGGET: Pemberdayaan Masyarakat Melalui Pengolahan Ikan Menjadi Nugget - animah animah; Akram Akram; Suryantara Adhitya Bayu Suryantara (Buletin SWIMP, 2022)
Catfish is the main commodity in Karang Bayan Village, West Lombok Regency, West Nusa Tenggara. So far, catfish farmers only sell their fish in the form of fresh fish so that the income received is relatively small. Therefore, it requires assistance to increase the economic activity of these fish farmers. This service activity aims to increase the understanding of creating added value for processed fish products for mothers in Karang Bayan Village, by providing knowledge about fish processing production techniques and calculating production costs and appropriate marketing techniques in order to generate optimal income. The method used is to conduct entrepreneurship training, including lectures, questions and answers. Demonstration, practice or practice, display. The results of the training showed that the women in Karang Bayan Village were able to process catfish into fish nuggets. In addition, they also understand the production techniques of processing fish nuggets by calculating production costs and appropriate marketing techniques to optimize income through social media as a sales and promotion medium.